Peningkatan Kreativitas Anak Yatim Piatu dengan Melukis Totebag Sebagai Pengganti Kantong Plastik - Tria Septia Miasari; Dewi Rochmayanti; Alya Putri Wulandari; Lailatus Syahri Syarifah; Luisa Fernanda Putri; Risma Pamella Septian (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The ever-increasing use of plastic bags has caused serious problems for the environment. Plastic waste is a material that is difficult to recycle and evaporate so that it can damage the environment. To overcome these issues, this community service activity conducts painting training on tote bags media as an alternative to reduce the use of plastic bags when shopping. This training aims to educate participants about the negative impact of plastic bags and provide skills and train creativity in creating bags that can be used repeatedly. This community service activity involved children from the LKS-A program at the Yayasan Sejubah Insan mulia. In this session, participants learned the techniques of painting and designing tote bags, so they not only gained knowledge, but also practical experience. The results of the training showed that participants became more aware of the importance of reducing the use of plastic and preferring tote bags as a replacement.